Robust design under cumulative damage due to dynamic failure mechanisms. Issue 5 (21st June 2021) - Engel, Avner; Teller, Amit; Shachar, Shalom; Reich, Yoram
Abstract: The purpose of this paper is to broaden the practical notion of Taguchi's Quality Loss Function (QLF) from a static, one‐stage concept into a dynamic time‐varying tool. Taguchi challenged the old‐age notion of engineering tolerance and proposed a quadratic QLF that quantifies loss to society, caused by deviation of products and systems from their target values. Accordingly, design engineers attempt to set each technical parameter to minimize such systems' losses. Traditionally, failure mechanisms are assumed to affect systems' performance stochastically under a steady state. So often, technical parameters are set at the mid‐point between the lower and upper specification limits where they are least likely to cause a system failure. However, in reality, many failure mechanisms affect systems over time in a predictable and directional manner rather than stochastically. Such mechanisms are designated as "Directional Degrading Failure Mechanisms" . The paper describes an optimized robust design method based on setting the operating points of technical parameters to explicitly counteract the effects of such failure mechanisms. Then, the paper describes how to minimize the lifetime societal loss of a given system utilizing a cardiac pacemaker system. The consequence of this approach suggests an extension to the Taguchi's QLF from its current static confines to a dynamic, time‐varying concept achieving, in our example, ≈65% reduction in lifetime societal losses.